Activist Turns Professional: Living the Tensions. (Concept: The Journal of Contemporary Community Education Practice Theory, 2014)
When practitioners are personally active in struggles or campaigns, tensions arise out of the intersection between radical politics and particular professional practices in the field of Community Education. I will use personal reflections of involvement in political activism and campaigns while completing the Community Education degree in University of Edinburgh to explore what these tensions are and what could be the constructive ways to navigate them.For the purpose of this article, I will use two ideal roles: ‘the activist’ and ‘the professional’. My aim is not to define and compare these roles exhaustively but rather to use them as a tool to explain and clarify my position. The notion of ‘the activist’ serves the purpose of conceptualising most of my personal identity and behaviour in the last few years. From a cultural context of grassroots environmental and anti-capitalist (direct) action, I have been involved in student campaigning for environmental and social justice, engaging in actions that range from petitions, media stunts and educational activities to industrial action and occupations.